Terapi Nebulasi pada Pasien Anak dengan Bronkiolitis - Muhammad, Gian Rasyiddin; Allenidekania, Allenidekania; Rustina, Yeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine which nebulization therapy is effective for improving respiratory status and reducing the length of stay in children with bronchiolitis. The research method used was a literature search using six databases: PubMed, ProQuest, ScienceDirect, Scopus, Sage Journals, and Embase. The results of the study showed that the average age of the children who were respondents was 0-24 months. Eight articles showed that all therapy options could improve the child's respiratory status, but not all significantly reduced the length of stay. In conclusion, nebulization therapy that can be used in pediatric patients with bronchiolitis to improve the child's respiratory status includes hypertonic saline (HS), normal saline (NS), magnesium sulfate (MgSO4), interferon α1b (IFN α1b) In, In and In racemic epinephrine (RE). , while nebulized therapy that can reduce the length of stay is racemic epinephrine (RE) and hypertonic saline (HS).This study aims to determine which nebulization therapy is effective for improving respiratory status and reducing the length of stay in children with bronchiolitis. The research method used was a literature search using six databases: PubMed, ProQuest, ScienceDirect, Scopus, Sage Journals, and Embase. The results of the study showed that the average age of the children who were respondents was 0-24 months. Eight articles showed that all therapy options could improve the child's respiratory status, but not all significantly reduced the length of stay. In conclusion, nebulization therapy that can be used in pediatric patients with bronchiolitis to improve the child's respiratory status includes hypertonic saline (HS), normal saline (NS), magnesium sulfate (MgSO4), interferon α1b (IFN α1b) In, In and In racemic epinephrine (RE). , while nebulized therapy that can reduce the length of stay is racemic epinephrine (RE) and hypertonic saline (HS). Keywords: Children, Bronchiolitis, Length of Hospitalization, Nebulization, Respiratory Status